2021
DOI: 10.1002/jmd2.12261
|View full text |Cite
|
Sign up to set email alerts
|

Comparing nitisinone 2 mg and 10 mg in the treatment of alkaptonuria—An approach using statistical modelling

Abstract: Background: Outcomes from studies employing nitisinone 10 mg and 2 mg in alkaptonuria were compared. Patients and methods: Sixty-nine patients in each of the nitisinone (10 mg daily) and controls of suitability of nitisinone in alkaptonuria 2 (SONIA 2), as well as 37 and 23 in nitisinone (2 mg daily) and control cohorts at the National Alkaptonuria Centre (NAC), respectively, were followed up for 4 years. Severity of alkaptonuria (AKU) was assessed by the AKU Severity Score Index (AKUSSI). 24-h urine homogenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 25 publications
1
10
0
Order By: Relevance
“…sTYR thresholds in NIT-treated adult AKU patients are more pragmatic as most of these patients are habituated to eating normally. In the United Kingdom National Alkaptonuria Centre, a specialist dietician manages the tyrosinaemia, to defined sTYR thresholds (Table S8), employing 7-day food diaries and fasting sTYR monitoring [27] . Daily dietary protein requirements designed to meet the need for limiting amino acids methionine, tryptophan, threonine and lysine [28] , [29] , result in obligate excess consumption of PHE and TYR.…”
Section: Discussionmentioning
confidence: 99%
“…sTYR thresholds in NIT-treated adult AKU patients are more pragmatic as most of these patients are habituated to eating normally. In the United Kingdom National Alkaptonuria Centre, a specialist dietician manages the tyrosinaemia, to defined sTYR thresholds (Table S8), employing 7-day food diaries and fasting sTYR monitoring [27] . Daily dietary protein requirements designed to meet the need for limiting amino acids methionine, tryptophan, threonine and lysine [28] , [29] , result in obligate excess consumption of PHE and TYR.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, a study conducted for four weeks proved the dose-response relationship as increasing nitisinone dosage concentration results in the decrease of 24-hr urinary HGA levels with the maximal effect obtained at 8 mg dose, which showed a 98.8% reduction in urinary HGA levels [ 5 ]. Another study found the same results at a 10 mg dose, which the European Medicines Agency has authorized to treat adult alkaptonuric patients [ 11 ].…”
Section: Nitisinone; a Promising Agent For Alkaptonuriamentioning
confidence: 64%
“…Results from the SONIA 2 trial, as well as the UK's National Alkaptonuria Centre (NAC), have demonstrated that once‐daily nitisinone is well tolerated and effective in reducing urinary excretion of HGA and slowing disease progression. 6 , 11 …”
Section: Introductionmentioning
confidence: 99%
“…Results from the SONIA 2 trial, as well as the UK's National Alkaptonuria Centre (NAC), have demonstrated that once-daily nitisinone is well tolerated and effective in reducing urinary excretion of HGA and slowing disease progression. 6,11 With nitisinone now approved as a treatment for AKU, 12 improving the cAKUSSI as a flexible and reliable tool to measure disease progression and treatment response globally is important for monitoring the realworld efficacy of nitisinone as well as any future treatments. A more flexible AKUSSI may be of particular relevance to registries and large cohort studies where the availability of equipment and clinical expertise is likely to vary across participating sites.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation